2009
DOI: 10.1177/1043463109337097
|View full text |Cite
|
Sign up to set email alerts
|

Club Goods and Post-Disaster Community Return

Abstract: Hurricane Katrina caused over one hundred billion dollars in property damage in the Greater New Orleans region. Although much attention has been paid to why particular communities have begun to recover and others have failed to rebound, very little attention has been paid to how the communities that have recovered actually went about doing so. This paper attempts to close that gap by examining how the church provision of club goods can foster social cooperation and community redevelopment in the wake of a disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(52 citation statements)
references
References 36 publications
1
49
0
2
Order By: Relevance
“…ChamleeWright and Storr ( ), Chang (2010 and (Kennedy, 2009) identified that keeping the community together and involving them in collective activities (such as social gatherings, participation in reconstruction and recovery work) and providing psychological support trigger them to recover from the trauma incurred after a disaster. They also fuel the determination to support the recovery process and move forward (Kennedy, 2009, Chamlee-Wright and Storr, 2009. The recovery effort following the Victorian Bushfires portrayed a good attempt at psycho-social recovery of affected people through the provision of "case managers" for each family to provide individualised information and resources to support recovery, as well as through providing services such as counselling, youth support, children support, men's getaways, memorial services, and community events (VBRRA, 2010).…”
Section: Community Recoverymentioning
confidence: 99%
“…ChamleeWright and Storr ( ), Chang (2010 and (Kennedy, 2009) identified that keeping the community together and involving them in collective activities (such as social gatherings, participation in reconstruction and recovery work) and providing psychological support trigger them to recover from the trauma incurred after a disaster. They also fuel the determination to support the recovery process and move forward (Kennedy, 2009, Chamlee-Wright and Storr, 2009. The recovery effort following the Victorian Bushfires portrayed a good attempt at psycho-social recovery of affected people through the provision of "case managers" for each family to provide individualised information and resources to support recovery, as well as through providing services such as counselling, youth support, children support, men's getaways, memorial services, and community events (VBRRA, 2010).…”
Section: Community Recoverymentioning
confidence: 99%
“…In our view, the literature on post‐Katrina recovery requires greater attention to sense of place and to the role that place attachment and dependence can play in motivating people to return and attempt to rebuild their communities. In our earlier study of post‐Katrina recovery in the New Orleans East Vietnamese community, sense of place, specifically the view that New Orleans was thought of as a second homeland for first‐ and second‐generation Vietnamese immigrants, was frequently mentioned as the reason they returned (Chamlee‐Wright & Storr, forthcoming a). An important question generated by this earlier work is whether sense of place would emerge as a critical factor in explaining the recovery efforts of Ninth Ward residents given the very real structural obstacles to recovery that exist in their communities and the negative perceptions of their neighborhoods that are frequently voiced by outsiders.…”
mentioning
confidence: 99%
“…In our work examining the reasons why and strategies by which people return to their communities following a devastating disaster, Storr and I find that mental models attributing a unique and positive sense of place (to an otherwise ordinary neighborhood), mental models attributing to government particular intentions and capacities for providing rebuilding assistance, and mental models of "God's divine plan" have all significantly shaped individual strategies and widespread patterns of postdisaster recovery (Chamlee-Wright and Storr 2009a,2009b, 2010ChamleeWright 2010a). But in such cases, when the mental models diverge so significantly from the investigator's mental models, indwelling will not be adequate if we are to understand how subjects' mental models shape broader social patterns.…”
Section: The Case For Qualitative Methods As a Means Of Operationalizmentioning
confidence: 96%